A mobile setup for simultaneous and in situ neutron reflectivity, infrared spectroscopy, and ellipsometry studies - Busch, Christian; Nagy, Béla; Stöcklin, Andreas; Gutfreund, Philipp; Dahint, Reiner; Ederth, Thomas (Review of scientific instruments, 2022)
Neutron reflectivity at the solid/liquid interface offers unique opportunities for resolving the structure-function relationships of interfacial layers in soft matter science. It is a non-destructive technique for detailed analysis of layered structures on molecular length scales, providing thickness, density, roughness, and composition of individual layers or components of adsorbed films. However, there are also some well-known limitations of this method, such as the lack of chemical information, the difficulties in determining large layer thicknesses, and the limited time resolution. We have addressed these shortcomings by designing and implementing a portable sample environment for in situ characterization at neutron reflectometry beamlines, integrating infrared spectroscopy under attenuated total reflection for determination of molecular entities and their conformation, and spectroscopic ellipsometry for rapid and independent measurement of layer thicknesses and refractive indices. The utility of this combined setup is demonstrated by two projects investigating (a) pH-dependent swelling of polyelectrolyte layers and (b) the impact of nanoparticles on lipid membranes to identify potential mechanisms of nanotoxicity.
Gesehen am 17.03.2023